Heavy Metal Residues and Microbial Status of Farmed and Channeled Cat Fish - Ebied, NA; Abdou, MS; Abass, ME; Kassab, AS (Journal of the Hellenic Veterinary Medical Society, 2024)
The purpose of the study was to look into the bioaccumulation of Cu, Cd, Pb, Mn, Fe and Zn in the muscles and livers of Clarias gariepinus catfish from farms and channels sources of River Nile in Kafr El-Sheikh province, Egypt, with microbiological evaluation of fish quality, and detection of Shiga toxin genes (stx1, stx2), and metal resistant genes (MRGs) in E. coli isolated and identified as Shiga toxin-producing E. coli (STEC) from fish muscles to predict the crucial hazards on consumers’ health from fish of both sources. The results showed increased metal levels in the tissues and liver of farmed fish than in the channeled, especially Pb detected by very high concentrations (16.39±1.26 and 11.90±1.68) mg/kg in 20% of examined muscles and liver samples of farmed fish, all detected levels of Pb were exceeded the permissible limits (PLs). Pb was not detected in the channel source. Mn, Fe and Zn were detected in all samples of both sources by (100%), but Mn and Fe only exceeded the PLs, while Zinc was with values lower than PLs. The (TBC), (TCC), Contamination rates with E.coli, STEC, and E.coli with (nccA and czcD) were found also significantly higher (p < 0.05) in examined muscle samples from farmed than channeled source. Stx2, nccA, and czcD genes were detected by 10%, 30%, and 20% respectively from identified STEC samples. In conclusion, farmed catfish had higher levels of heavy metals and bacterial pollution than channel catfish,in addition metal resistant bacteria may be considered an indicator of heavy metal contamination in the aquatic ecosystem